Development of Obsessive-Compulsive Disorder in Medical Versus Dental Practitioners During Covid 19 Pandemic - Hira Butt, Syed Ghyour Ali Mohsin, Bilal Khalid, Zainab Waheed, Waleed Ahmad, Maria Jabbar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To identify the development of symptoms of obsessive-compulsive disorder in medical and dental practitioners during COVID 19 pandemic. A cross-sectional comparative study was conducted on 146 medical and dental practitioners. The study was conducted at College of Dentistry, Sharif Medical and Dental College, Lahore and Sardar Begum dental college, Peshawar from August 2021 to June 2022. The Obsessive-compulsive inventory scale with a Cronbach alpha value of 0.966 was used for data collection. The association of the presence of symptoms of checking (p=0.027), neutralizing (p=0.021), and hoarding (p=0.009) with the area of practice was statistically significant while it was non-significant for the symptoms of washing (p=0.332), obsessing (p=0.093), ordering (p=0.093) and doubting (p=0.099). The presence of obsessive-compulsive disorder and the area of practice was also non-significant (p=0.300). The percentage of all seven symptoms in medical practitioners was higher in comparison to the dental practitioners. It was seen that a higher percentage of medical practitioners developed obsessive-compulsive disorder in comparison to dental practitioners during the COVID 19 pandemic Keywords: Obsessive-compulsive disorder, medical practitioners, Dental practitioners, COVID-19 pandemic